DEVELOPMENT OF TRAINING COURSE ON SYSTEM CONTROL ELECTRIC MOTORCYCLE CONVERSION FOR MOTORCYCLE MECHANICS - Manknong, Sodsai; Yanil, Surawut; Oungthong, Metha (Journal of Social Science and Cultural, 2025)
This research article aims to investigate foundational information regarding the development of a training course for a modified electric motorcycle motor control system for motorcycle mechanics, to review the draft course, to develop a supplementary skill training kit, to trial the course, and to evaluate its effectiveness. This study employs a research and development approach comprising five phases. The sample group consists of 25 motorcycle mechanics selected through voluntary sampling method. The research instruments used include 1) a recording form 2) an interview form 3) the training course 4) a supplementary skill training kit and 5) the evaluation forms. The statistical methods used for data analysis include percentage, mean, standard deviation, and t-test. The research findings reveal that the core components of the training course for the modified electric motorcycle motor control system for motorcycle mechanics include the background and significance of the course, the course objectives, the course structure comprising lessons, topics, subtopics/content, behavioral objectives, and training duration, training activities, training media, and assessment and evaluation. The evaluation of the draft course identified 7 components: the background and significance of the course, course objectives, the course structure, course content, training activities, training media, and assessment and evaluation. These components were deemed highly appropriate. Regarding the development of the supplementary skill training kit, 4 step skills assessment form was employed, including preparation for practice, practice process, time spent on practice and stage of performance of the trainees. The overall mean score exceeded the established criteria. The results from the trial of the training course indicated that the skill assessment outcomes were higher than the specified criteria. Additionally, the evaluation of the training course across four dimensions: feasibility, usefulness, appropriateness, and accuracy were rated at the highest level overall.